Filsafat Ilmu sebagai Dasar Berpikir Kritis dan Ilmiah - Sukma, Agry Pradiyas (Lembaga Yasin AlSys, 2025)
The branch of philosophy known as the philosophy of science explores the nature of knowledge in depth, including its structure, methods, and validity. The philosophy of science plays a central role in shaping critical and scientific thinking, particularly in the context of education and scholarly development. This study aims to examine how the philosophy of science can serve as a foundation for cultivating critical and scientific thinking, as well as its impact on the learning process and knowledge development. A descriptive qualitative approach was used, with literature review as the primary data collection method. The findings reveal that the philosophy of science helps individuals understand the limits of knowledge, distinguish between what is known and unknown, and foster a healthy skepticism toward scientific claims. Moreover, it encourages the development of systematic and logical arguments. Scientific thinking requires a systematic, objective, and testable process, while critical thinking involves evaluating assumptions, logic, and supporting evidence. Therefore, a deep understanding of the philosophy of science is essential for enhancing intellectual capacity, fostering epistemic responsibility, and producing valid and scientifically accountable knowledge.